Utilization of Passion fruit hulls (Passiflora edulis Sims f. edulis Deg) as component of complete feed for growing Kacang goats - Kiston Simanihuruk (Indonesian Center for Animal Research and Development (ICARD), 2009)
Processing of passion fruit (Passiflora edulis Sims f. edulis Deg) to produce passion fruit juice produce passion fruit hulls that is potential for feedstuff. Twenty male kacang goats (average initial body weight 17±1.24 kg) were used in an experiment to study the effect of utilization of passion fruit hulls as feed component in the complete pellet ration on their growth. The experiment was arranged in completely randomized design consisting of 4 diets and 5 replications. Animal were randomly allocated into 4 diets (0, 15, 30, 45% level of passion fruit hulls). Each diet contained 14% crude protein and 2550 Kcal kg-1 metabolism energy. The ration was offered at 3.8% of body weight based on dry matter. The result of the experiment showed that all variables observed were not affected by level of passion fruit hulls (P>0.05). Average daily gain and feed efficiency tended to decrease with the increase level of passion fruit hulls. The highest dry matter, organic matter and N intake (768,78 g h-1 d-1; 687,37 g h-1 d-1 and 17,22 g h-1 d-1 respectively) were found from R1 treatment (15% level of passion fruit hulls). It was concluded that passion fruit hulls can be used till 45% level in the diet of Kacang goat. Key Words: Passion Fruit, Complete Pellet Ration, Kacang Goat